From Soybean Oil to Signaling Molecules: Oxylipins as Pharmacologically Active Lipids Modulating Liver and Metabolic Health - Kamlesh Sahu; Trilochan Satapathy; Poonam Sahu; Abhisek Satapathy; Om Chandrakar (Glucolipid Metabolic Disorders, 2026)
Introduction: Glucolipid metabolic disorders, including Metabolic Dysfunction- Associated Steatotic Liver Disease (MASLD), formerly known as Non-Alcoholic Fatty Liver Disease (NAFLD), insulin resistance, Type 2 Diabetes Mellitus (T2DM) and obesity, are characterized by dysregulated hepatic lipid metabolism, impaired glucose homeostasis and systemic energy imbalance. Oxylipins, a diverse class of oxygenated bioactive metabolites derived from Polyunsaturated Fatty Acids (PUFAs), have emerged as key lipid mediators that link dietary fatty acid composition to intracellular metabolic signaling pathways. Soybean oil, a major dietary source of linoleic acid and α-linolenic acid, provides abundant substrates for oxylipin biosynthesis via cyclooxygenase (COX), lipoxygenase (LOX), cytochrome P450 (CYP), and non-enzymatic oxidative pathways. This review comprehensively examines the mechanistic roles of soybean oil-derived oxylipins in regulating hepatic glucolipid metabolism and highlights their potential as therapeutic targets and diagnostic biomarkers for glucolipid metabolic disorders. Methods: Relevant peer-reviewed studies were identified through a comprehensive review of experimental, clinical, and lipidomics-based literature. Evidence related to oxylipin biosynthesis, receptormediated signaling, metabolic regulation, oxidative stress, inflammation, and glucolipid metabolic disorders was critically evaluated and systematically synthesized to provide an integrated mechanistic framework and highlight the therapeutic and diagnostic potential of oxylipins in metabolic diseases. Results: Current evidence indicates that oxylipins play pivotal roles in regulating glucolipid metabolism by activating G protein-coupled receptors and nuclear receptors, including Peroxisome Proliferator- Activated Receptor-α (PPARα), Peroxisome Proliferator-Activated Receptor-γ (PPARγ) and Liver X Receptors (LXRs). Through these signaling pathways, oxylipins regulate fatty acid oxidation, de novo lipogenesis, gluconeogenesis and insulin signaling, thereby maintaining metabolic homeostasis. Linoleic acid-derived oxylipins are generally associated with enhanced oxidative stress, mitochondrial dysfunction, chronic inflammation and insulin resistance. In contrast, cytochrome P450 (CYP)-derived epoxy-fatty acids exhibit anti-inflammatory, antioxidant and insulin-sensitizing properties that promote hepatic metabolic homeostasis. Moreover, disease-specific alterations in oxylipin profiles are strongly associated with hepatic lipid accumulation, lipid peroxidation and the progression of metabolic dysfunction, highlighting their potential as diagnostic biomarkers and therapeutic targets for glucolipid metabolic disorders. Discussion: The available evidence indicates that oxylipins exert both protective and detrimental effects, depending on their biosynthetic origin, fatty acid precursor and receptor specificity. Although considerable progress has been made in elucidating oxylipin-mediated metabolic signaling, variations in experimental models, analytical methodologies and clinical populations continue to limit the translation of these findings into therapeutic applications. Future studies integrating standardized lipidomic profiling with mechanistic investigations and well-designed clinical studies are essential to validate oxylipin-based biomarkers, establish causal relationships and facilitate the development of targeted therapeutic strategies for glucolipid metabolic disorders. Conclusion: Oxylipins are key regulators of hepatic glucolipid metabolism, linking dietary lipid metabolism with oxidative stress, inflammatory signaling and insulin sensitivity. Their diverse biological functions and context-dependent effects underscore their potential as diagnostic biomarkers and therapeutic targets for MASLD, insulin resistance, type 2 diabetes mellitus, obesity and other glucolipid metabolic disorders.